2009
DOI: 10.1002/joc.2016
|View full text |Cite
|
Sign up to set email alerts
|

Snow trends in Northern Spain: analysis and simulation with statistical downscaling methods

Abstract: ABSTRACT:In this study we analyze and simulate (with statistical downscaling techniques) the snow trends observed in the Northern Iberian Peninsula using daily snow occurrence (DSO) data from a network of 33 stations ranging from 60 to 1350 m. We first analyze the annual snow frequency measured as the annual number of snow days (NSD), obtaining a significant decreasing trend since the mid-seventies with a NSD reduction of about 50%; moreover, this magnitude is similar for low and high stations and for winter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
5
24
0
1
Order By: Relevance
“…on the slopes). However, in terms of the total water equivalent that is not accounted for, it is likely the northern areas and the Pyrenees range experience more total undercatch because of the relatively large portion of winter precipitation occurring in these mountains as snowfall (Pons et al, 2010;Bootey et al, 2013;Buisan et al, 2014). It is also important to note that, in general, snowfall in Spain occurs very infrequently at temperatures colder than −3 • C, and the average 1 h wind speed during snowfall events is lower than 30 km h −1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…on the slopes). However, in terms of the total water equivalent that is not accounted for, it is likely the northern areas and the Pyrenees range experience more total undercatch because of the relatively large portion of winter precipitation occurring in these mountains as snowfall (Pons et al, 2010;Bootey et al, 2013;Buisan et al, 2014). It is also important to note that, in general, snowfall in Spain occurs very infrequently at temperatures colder than −3 • C, and the average 1 h wind speed during snowfall events is lower than 30 km h −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the Spanish climate record, winter precipitation is persistently underestimated, especially in areas subject to frequent snowfall (Pons et al, 2010;Buisan et al, 2014). This underestimation could affect previous studies of solid precipitation, especially if the period of time considered was associated with significant winter precipitation extremes Vicente-Serrano et al, 2011;Añel et al, 2014;Cortesi et al, 2014;Buisan et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated a negative trend in the occurrence of snow days in the northwest of the Iberian Peninsula (Pons et al 2009), and a substantial decrease in the duration and depth of the snowpack, which is causing a decrease and shift in spring peak flows (López-Moreno 2005, López-Moreno et al 2008. Snowmelt is a general component of river regimes in the headwaters of the Duero basin (Morán-Tejeda et al 2011b), and the decrease of spring high flows is likely to be related to the reduction in snowpack given the increasing temperatures documented in the region in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, results are inconclusive and seem to be highly affected by the period of analysis. Pons et al (2010) analysed snow trends in northern Spain using daily snow occurrence data from a network of 33 stations. They showed a significant decreasing trend in the annual number of snow days since the mid-1970s to 2001, with a reduction of about -50%.…”
Section: Snow Precipitationmentioning
confidence: 99%